Consumer Demand for Environmental, Social, and Ethical Information in Fishery and Aquaculture Product Labels - Peiró-Signes, Angel; Miret-Pastor, Lluís; Galati, Antonino; Segarra-Oña, Marival (Frontiers in Marine Science, 2022)
Customers attention to sustainability labels in fish and aquaculture products (FAPs) has been increasing in last decades and the industry has adapted to this growing interest adopting fish ecolabels. However, there is a growing interest to widen the sustainability concept to include the social and ethical information of the fish and aquaculture industry and to go further from the voluntary approach on the labelling of these aspects in fish and aquaculture products. For this reason, using data from 2021 Eurobarometer and using machine learning techniques, we disentangle the characteristics of the FAPs buyers that consider the importance of environmental impact, ethical, and social information appearing on FAPs labelling. The results confirmed that most of the consumers who consider environmental, social, and ethical aspects when buying FAPs also think this information should be labeled. In line with other works, young, educated, and environmentally aware consumers in high income countries are more likely to request this information in the FAPs label. One interesting finding of the study relates with the asymmetric impact of the variables and the important group of respondents that do not consider these aspects but also advocate to include them in the FAPs label. The study outcomes can be beneficial for policy-makers to design future public policies regarding FAPs labeling, as well as to be taken into consideration in the marketing policies of fishery and aquaculture producers and retailers.